ANALISIS KEBIJAKAN PEMBENTUKAN SPORC DAN IMPLEMENTASINYA DALAM PEMBERANTASAN ILEGAL LOGING DI INDONESIA (STUDI KASUS DI SULAWESI SELATAN) - Muhammad Ashlam Tangngalangi; Hariadi Kartodihardjo; Iin Ichwandi (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
Establishment of Forest Police Rapid Response Unit (SPORC) is the government's policy on law enforcement efforts in the field of forestry. Since its formation in 2005 it has been kown as its field implementation, while the practice of illegal logging still occurs. This study aims to reveal what the policy arguments underlying the formation, how it was implemented - especially SPORC Brigade Anoa in South Sulawesi (SPORC Anoa), and what can be recommended for the law enforcement to be more effective. The results showed that the problem is defined thus giving birth of SPORC formation policy is the deforestation is at very alarming rate, while the existing forest protection agencies have not been effective. In terms of quality, SPORC Anoa performance has not met expectations, most of the suspects were prosecuted to court are farmers. Lack of community involvement in the prevention and eradication of illegal logging, and poor relationships between central and local forestry agencies, mainly due to sharp differences about perception of forest area status. Completion of forest area status in Indonesia being important recommendations that need to be addressed. Forestry Law that is not up to date anymore, and institutions that have not been fully independent, caused low quality of case handling